Concepts of Human Development As A Dilemma of Postindustrial Society - Qanoatovich, Shirinov (Indonesian Journal of Public Administration Review, 2025)
In the following article the ideas of human development as a dilemma of postindustrial society are discussed from the viewpoint of recent tendencies in the region It has been argued that the development of human capital in Central Asia relied on important factors such as fair social policy, green development, nation building, use of resource-efficient technologies, consistency of spiritual and educational reforms, close neighborliness and the establishment of strategic cooperation. The article focuses on research based on the factors of human development that shape socio-economic approaches and its importance in social life, the role of cliodynamics and its importance in the development of human capital, in contrast to research in this direction.